2022
DOI: 10.3390/ijms23042102
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as a Model to Study Vascular Elastic Fibers and Associated Pathologies

Abstract: Many extensible tissues such as skin, lungs, and blood vessels require elasticity to function properly. The recoil of elastic energy stored during a stretching phase is provided by elastic fibers, which are mostly composed of elastin and fibrillin-rich microfibrils. In arteries, the lack of elastic fibers leads to a weakening of the vessel wall with an increased risk to develop cardiovascular defects such as stenosis, aneurysms, and dissections. The development of new therapeutic molecules involves preliminary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 156 publications
(212 reference statements)
0
13
0
Order By: Relevance
“…The in vitro experiments suggest that SEP behaves as an analogue of hTE. To go further and initiate in vivo studies, we chose to use the zebrafish model that we recently reported as a relevant tool in the analyses of cardiovascular issues [39]. Specifically, we used the transgenic zebrafish reporter line Tg( fli1a :eGFP)/Casper, whose endothelial cells are fluorescent and enable vessel development observation in real time.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro experiments suggest that SEP behaves as an analogue of hTE. To go further and initiate in vivo studies, we chose to use the zebrafish model that we recently reported as a relevant tool in the analyses of cardiovascular issues [39]. Specifically, we used the transgenic zebrafish reporter line Tg( fli1a :eGFP)/Casper, whose endothelial cells are fluorescent and enable vessel development observation in real time.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing regenerative and non-regenerative hearts can inform treatment strategies for human heart diseases. In healthy adult humans, ventricular blood pressure is maintained at 120 mmHg, while in adult zebrafish, it is estimated to be only 2.5 mmHg [ 29 ]. Mammals deposit thick collagen layers to strengthen the ventricular wall against high blood pressure [ 30 ], whereas zebrafish generate a thin, loose collagen-rich scar during early heart regeneration [ 31 ], making the scarring easier to resolve.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they have a simpler circulatory system than mammals. Although the structure of the heart of zebrafish appears different, some of their electrocardiogram parameters are more comparable to those of humans than those of mice; heart rates are 120–180 beats per minute (bpm) in zebrafish, 300–600 bpm in mice, and 60–100 bpm in humans [ 3 , 4 , 5 ]. Both humans and zebrafish generate a repolarizing current during action potential (AP), using a similar rapidly activating delayed rectifier potassium current.…”
Section: Animal Disease Modelsmentioning
confidence: 99%
“…In the field of cardiovascular research, different environments may result in different heart structures; for example, zebrafish have one atrium and one ventricle, whereas mice and humans have two atria and two ventricles. The characteristics of heart function also vary [ 3 , 4 , 5 ]. Nevertheless, mice and rodents are most often used as models of cardiovascular disease because they are easy to handle, have lower upkeep costs, and maintain stricter strains, resulting in fewer genetic differences.…”
Section: Introductionmentioning
confidence: 99%